2022
DOI: 10.1109/tpel.2021.3101713
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Data-Driven Modeling Methodology for Fast and Accurate Transient Simulation of SiC MOSFETs

Abstract: To enable fast and accurate models of SiC MOS-FETs for transient simulation, a hybrid data-driven modeling methodology of SiC MOSFETs is proposed. Unlike conventional modeling methods that are based on complex nonlinear equations, data-driven Artificial Neural Networks (ANNs) are used in this paper. For model accuracy, the I-V characteristics are measured in the whole operation region to train the ANN. The ANN model is then combined with behavior-based equations to model the cutoff region and to avoid overfitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The static layer-to-layer capacitance of inductors with series winding is represented as (4), where the only difference is the radius of the conductor. Detailed derivation could be found in [20].…”
Section: A Round-cable-based Inductors With Two Windingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The static layer-to-layer capacitance of inductors with series winding is represented as (4), where the only difference is the radius of the conductor. Detailed derivation could be found in [20].…”
Section: A Round-cable-based Inductors With Two Windingsmentioning
confidence: 99%
“…Passive components are essential in power electronics converters [1], [2]. For the converters utilizing wide-bandgap devices [3], [4], the parasitic capacitance in magnetic components, including inductors [5], [6], transformers [7] and motors [8], is of significant importance due to the fast switching characteristics (high dv/dt value) of the wide-bandgap devices [8], [9]. It is reported that such parasitic capacitance can significantly contribute to the capacitive current during the switching transients [10] and may result in increased conducted noise and extra switching losses dissipated by the transistors [11]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, device modeling methods using machine learning, such as neural networks, have been proposed [30], [31]. These methods could accurately reproduce the electrical and thermal behavior of devices.…”
Section: Introductionmentioning
confidence: 99%
“…Various literature works studied the overshoots and oscillations of the SiC MOSFET during the switching transients. The influence of the source inductance and drain inductance on the overshoots is reported in Li et al (2016) and Yang et al (2022).…”
Section: Introductionmentioning
confidence: 99%